Assessment of knowledge, attitude and practices of universal precautions among medical and nursing students - C. S., Vinod Kumar; Prasad, Sonika Bindu; Gopalkrishnan, Ananya; G., Basavarajappa K.; Kalasuramath, Suneeta (International Journal of Research in Medical Sciences, 2019)
Background: Universal precautions is an approach to infection control to treat all human blood and certain human body fluids as if they were known to be infectious for HIV, HBV and other bloodborne pathogens. The CDC recommends Standard Precautions for the care of all patients, regardless of their diagnosis or presumed infection status. Health care personals are at risk of being exposed to blood-borne pathogens. The aim of the study to determine the knowledge, attitude and practice of medical and nursing students towards universal precautions. Methods: A cross-sectional survey was carried out at S. S. Institute of Medical Sciences and Research Centre, Davangere, Karnataka. The participants were medical and Nursing undergraduate students. A questionnaire was prepared based on the WHO and CDC guidelines on Universal Precautions and was validated and pre-tested before finalization. Degree of knowledge was ascertained by means of yes-no questions on each item being evaluated. Results: All students were aware of Universal precautions, but soundness of their knowledge is very poor. Compliance in Universal precautions is good to average in nursing students but poor to average in medical students. Conclusions: It can be concluded that interventions to improve Universal precautions among medical students, nursing students urgently needed. So, there is a need for developing strategies to promote the use of Universal precautions which take into account behaviour change and accuracy of knowledge including its integration into practice. Teaching universal precautions early in their curriculum is necessary for better learning and practices during their posting.